THE ATTEMPT OF LEONARD DEKKOM TO GAIN THE POWER IN GEOSTORM (2017): MACHIAVELLI’S PERSPECTIVE - Khairunnisa, Zahra Aamalia; Sumayah, Sumayah (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This research analyzed Leonard Dekkom’s attempt to gain power in the film Geostorm (2017) through Machiavelli’s perspective. This research aims to see how Machiavelli’s theory applies to the actions taken by Leonard Dekkom, the strategies used, and the motivations behind the sabotage of the Dutch Boy system. This research uses a descriptive qualitative method, collecting data through film analysis of scenes and dialogue to relate the findings. The results of this study show that Leonard Dekkom reflects Machiavellian traits, such as manipulation, cunning strategies, and tactics that override moral values to achieve his personal ambitions. Success in achieving power in politics prioritizes the goal over morality, such as Leonard Dekkom’s sabotage. This study concludes that Leonard Dekkom reflects the complexity of power politics, which is in line with Machiavelli’s thinking that prioritizes strategy and ambition over moral values.